Gastrointestinal Stomas - Neri, Vincenzo (IntechOpen, 2019)
Gastrointestinal stomas constitute an evident anatomical modification, but their perception by patients represents a serious and unacceptable alteration of the body schema. Esophagostomy, gastrostomy, and jejunostomy are usually temporary, but ileostomy and colostomy are permanent in many cases. Two purposes characterize the two types of intestinal stomas: to divert intestinal content and to allow enteral nutrition. The purpose of the stoma in the therapeutic program is surrounded by many misunderstandings and this notice given by surgeons is horrifying to patients. In this therapeutic scenario the enterostomal therapist plays a central role. This book pays great attention to the care of the stoma and its therapeutic role, but overall the need is to prevent diagnostic and therapeutic procedures for this surgical alteration to the body's anatomy.